A testing time for tsetse eradication? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Even with 100 years of experience and more than enough tools in the toolbox, the way forward for tsetse control continues to be a hotly debated subject. 'Tsetse eradication is a vision, control is a strategy' said one participant at a discussion...